Effect of legal awareness of hotel employees on their job satisfaction: Mediated by organizational trust - Karatay, Cem; Ozduran, Ali (Elsevier Sci Ltd, 2025)
Based on the Conservation of resources theory (COR), the purpose of this study was to analyze the correlation between legal awareness (LA), organizational trust (OT), and job satisfaction (JS) of hotel employees in T & uuml;rkiye. Legal awareness was measured in four categories (Union-collective bargaining law (UCBL), Social insurance and general health insurance law (SIGHIL), Labour law (LL), and Occupational health and safety law (OHSL)). Using a quantitative approach with a rating-scale questionnaire, data were acquired from 229 hotel employees working in three-, four-, and five-star hotels. The findings demonstrate that there is a positive relationship between legal awareness and job satisfaction and this relationship is mediated by organizational trust. In the research, theoretical and practical implications are highlighted, and various suggestions are made for new areas of investigation.
Keywords: Hotel employees; Legal awareness; Organizational trust; Job satisfaction